KEGIATAN EKSTRAKURIKULER KESENIAN ANGKLUNG SEBAGAI SARANA PENGEMBANGAN PERILAKU CINTA TANAH AIR - Aryanti Dwi Untari (Pendidikan Pancasila dan Kewarganegaraan, FKIP, Universitas Banten Jaya, 2018)
The low sense of patriotism student at school became the focus of the problem in this research. In addressing this, schools have a very important role in imparts values ​​and developing student’s patriotism behavior through various programs and activities was held in schools. This study aims to find out how the extracurricular activities of angklung arts can be used as a means of developing patriotism behavior. By using descriptive qualitative method, this research will examine the extracurricular activities of angklung art in developing patriotism behavior in SMA Negeri 24 Bandung. The subjects in this study are students of SMA Negeri 24 Bandung who follow the extracurricular activities of angklung arts. The results showed that the extracurricular activities of angklung art at SMAN 24 Bandung were able to inculcate the noble cultural values ​​through Sundanese cultural art, in which there are cultural values ​​that can foster a sense of pride and love towards the homeland of Indonesia. This can be seen from the student's patriotism behavior which is reflected in the daily activities of the school.